Reversed-Phase HPLC Method for Determination of Quercetin in Human Plasma - Vijaya Sri, K.; Ratna, J.Vijaya; Annapurna, A.; Ravi Kumar, B.V.V. (Asian Journal of Chemistry, 2010)
A simple reversed-phase liquid chromatography method was developed for the quantitative determination of quercetin. The method is simple, sensitive and highly selective and involves single extraction of drug from plasma in (4:1) ratio of methanol: DMSO. The mobile phase was pumped at a flow rate of 1.0 mL/min and the effluent was monitored at 370 nm. The retention time of quercetin was 2.72 min. The limit of detection of drug in plasma was found to be 0.2 μg/mL. The method was validated for its linearity, precision and accuracy.